Charge-swapping Q balls - Copeland, Edmund J.; Saffin, Paul M.; Zhou, Shuang-Yong (American Physical Society, 2014)
Q-balls are non-topological solitonic solutions to a wide class of field theories that possess global symmetries. Here we show that in these same theories there also exists a tower of novel composite Q-ball solutions where, within one composite Q-ball, positive and negative charges co-exist and swap at a frequency lower than the natural frequency of an individual Q-ball. These charge-swapping Q-balls are constructed by assembling Q-balls and anti-Q-balls tightly such that their nonlinear cores overlap. We explain why charge-swapping Q-balls can form and why they swap charges.